Natural history of the aortic wall changes in adults with the degenerative tricuspid aortic valve stenosis: the morphometric proofs and implications for echocardiography - Borović, Saša D.; Labudovic Borovic, Milica M.; Todorović, Vera N.; Rakočević, Jelena T.; Marinković-Erić, Jelena M.; Kostić, Jelena V.; Trifunović, Zoran; Milojević, Predrag S. (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. So far, no study has been focused exclusively on the tricuspid aortic valve stenosis (TAV) in the aorta without severe dilatation and none has aimed at correlating the high mycroscopy findings with the echocardiographic parameters. This research was conducted on the postulate that detecting the histopathological changes of different severity in the aortic wall could tailor decision about an aortic surgery. The aim of this study was to grade the histopathological changes in the wall of the nonseverely dilated ascending aorta in patients with the severe, calcific TAV stenosis and to correlate them with the echocardiographic parameters in order to analyze when the ascending aorta should be replaced simultaneously with the aortic valve replacement (AVR). Methods. The samples from 37 patients subjected to the AVR and the samples from the control group were analyzed morphologically. The echocardiographic parameters obtained in the TAV stenosis patients were preoperatively correlated with the morphological data, age and gender, diameters of the ventriculo-aortic junction (AA), the sinus Valsalvae (SV) and sinotubular junction (STJ), the largest diameter of the visualized ascending aorta (AscA), the sinus Valsalvae index (SVI) and AscA/AA index. Results. We confirmed morphometrically the exact region of the hemodynamic stress influence with the mathematical distinction in comparison to the controls. In this region, the gradual elastic lamellae disruption was proved by a statistically significant difference through the 3 grades. The elastic skeleton alterations were potentiated with aging and in females. The morphometric parameters of the ascending aorta wall statistically significantly correlated with the echocardiographic parameters: AA, SV, AscA and SVI. The echocardiographic parameters tended to be higher in the most severe grade 3, in the patients younger than 65 years of age. The AscAof more than 4.5 cm was associated with the irreversible morphological defects in these patients. Conclusion. The hemodynamic stress induced by the TAV stenosis leads to the ascending aorta elastic lamellae disruption that could be histopathologically graded and correlated with the echocardiographic parameters of the ascending aorta providing a potential tool for decision-making process in cases when the ascending aorta replacement is considered simultaneously with the AVR.
Keywords: aorta; aging; aortic valve stenosis; echocardiography; heart valve prosthesis; histological techniques; tissues